1986
DOI: 10.1111/j.1365-2311.1986.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between larval density, adult size and egg production in the cowpea seed beetle, Callosobruchus maculatus

Abstract: 1. The eggs of the cowpea seed bettle Callosobruchus maculatus (Fab.) are attached to cowpeas. On hatching, the larvae penetrate the testa and remain in the seed until development is complete and adult eclosion has occurred. The adults do not need to feed and were not allowed to do so.2. Strains from Brazil and Nigeria can produce more than twelve adults from a seed bearing numerous eggs, whereas a strain from the Yemen Republic rarely produced more than three.3. In all three strains the mean weight of the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 9 publications
7
94
0
1
Order By: Relevance
“…Female fitness is dependent on their fecundity, which is directly dependent on body size (Dendy and Credland, 1991;Colegrave, 1993;Callejas, 1996), while male size although not so directly linked to reproductive success, can affect mating success (Savalli and Fox, 1998). Earlier studies with C. maculatus found that seed size and the initial number of eggs on the seed influenced the weight of emerging adults (Credland et al, 1986;Giga and Smith, 1991;Colegrave, 1995). For Z. subfasciatus, we found that seed size mostly affects female but not male size and only on the smaller wild seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Female fitness is dependent on their fecundity, which is directly dependent on body size (Dendy and Credland, 1991;Colegrave, 1993;Callejas, 1996), while male size although not so directly linked to reproductive success, can affect mating success (Savalli and Fox, 1998). Earlier studies with C. maculatus found that seed size and the initial number of eggs on the seed influenced the weight of emerging adults (Credland et al, 1986;Giga and Smith, 1991;Colegrave, 1995). For Z. subfasciatus, we found that seed size mostly affects female but not male size and only on the smaller wild seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Such assessment is functional. In most beetle populations, more than one weevil can develop in each seed; nevertheless, each additional larva faces both a greater risk of not obtaining sufficient resources for successful development or, if development is successful, a reduction in fecundity (Mitchell, 1975;Credland et al, 1986). …”
Section: Benefits Of Marking Hostsmentioning
confidence: 99%
“…Previous works have shown that, as well as reducing the survival of larvae to maturity; larval competition also negatively influences the fecundity of surviving adults (Colegrave, 1993). In addition, larval competition does not influence adult fecundity, independent of its effect on adult weight (Credland et al, 1986;Colegrave, 1993). Consequently, our results raise two fundamental questions: how does this oviposition behaviour confer a fitness advantage; and how is it adaptive for the females that choose to cluster eggs in a stored grain environment.…”
Section: Discussionmentioning
confidence: 58%